Pendekatan Konseptual Hubungan Kepemimpinan, Budaya, Strategi Dan Kinerja Organisasi - M Hudori (JURNAL CITRA WIDYA EDUKASI, 2019)
This paper will present a conceptual framework that describes the relationship between the variables of leadership, culture, strategy, and performance. Social organizations tend to follow the five phases of organizational growth being addressed by Greiner (1972), as described Hatch (1997), namely: 1) an organization that exists because of the creativity of a few individual; 2) the existence of organizational growth through referrals from its leader, 3) the emergence of the crisis in the form of each region wanted to walk on their own without the involvement of the center; 4) the growth of the organization is characterized by the lack of coordination between central and local to control the crisis; and 5) developing the organization on the basis of collaboration which meant that every leader there is openness. This paper will also present some theoretical concepts of Organizational Behavior, Organizational Culture, Leadership, and Strategic Management. Finally, several studies have looked at the purpose of the relationship variables of leadership, culture, strategy, and performance is expected to develop research purposes.